Ar(c)tivism and Policing: Unveiling the Theatrics of Justice and Resistance in Nigeria’s S<semantics><mover>ọ̀</mover></semantics>r<semantics><mover>ọ̀</mover></semantics>-Sókè Movement - Friday Gabriel; Taiwo Afolabi (Arts, 2025)
The S<semantics><mover>ọ̀</mover></semantics>r<semantics><mover>ọ̀</mover></semantics>-Sókè movement, sparked by Nigeria’s 2020 #EndSARS protests, represents a pivotal stand against systemic injustice, with its Yoruba rallying cry “S<semantics><mover>ọ̀</mover></semantics>r<semantics><mover>ọ̀</mover></semantics>-sókè” (“Speak Up” or “Speak Louder”) capturing the collective demand to end police brutality, notably, by the Special Anti-Robbery Squad (SARS). This study employs Digital Artivism as its theoretical lens to investigate the fusion of art and activism within the movement, analyzing how creative and performative expressions amplified its message and mobilized diverse populations. Applying Feldman’s Model of Art Criticism, it dissects the theatrical elements of selected protest artworks, revealing their role in inciting resistance and fostering solidarity in the pursuit of justice. By situating S<semantics><mover>ọ̀</mover></semantics>r<semantics><mover>ọ̀</mover></semantics>-Sókè within global discourses on art and social justice, this research underscores its significance as a model of artivism’s power to challenge oppressive systems and inspire collective action. The critique of these artworks illustrates their lasting influence on Nigeria’s socio-political landscape and their resonance with worldwide struggles against systemic violence and inequality. Highlighting the transformative potential of theatrical activism, this study advances understanding of how digital artivism can unite voices, elevate causes, and drive societal change.